Perancangan UI/UX Design Website Papan Ajar Di Treeta Gama Solution Menggunakan Metode Design Thinking - Anisah Ayu Lestari; Tri Rochmadi; Dadang Heksaputra; Avrillaila Akbar Harahap (Jurnal Tata Kelola dan Kerangka Kerja Teknologi Informasi, 2026)
This study aims to design the user interface (UI) and user experience (UX) on the Treeta Gama Solution's Papan Ajar website using a Design Thinking approach. This method was chosen because it focuses on understanding user needs and behaviors in depth through the stages: empathize, define, ideate, prototype, and test. This study uses system usability scale testing and user evaluation with tools such as interactive prototypes and Google Form to collect feedback. The results of the study obtained from the SUS calculation of 75.5 fall into the feasible category with a grade B. The developed design is expected to provide a positive contribution in improving the quality of digital learning experiences. Keywords – Design Thinking,  Website, Papan Ajar,  UI/UX, SUS.